DNA Damage Response Regulation Alleviates Neuroinflammation in a Mouse Model of α-Synucleinopathy - Sazzad Khan; Himanshi Singh; Jianfeng Xiao; Mohammad Moshahid Khan (Biomolecules, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder marked by the degeneration of dopaminergic neurons in the substantia nigra, leading to decreased dopamine levels in the striatum and causing a range of motor and non-motor impairments. Although the molecular mechanisms driving PD progression remain incompletely understood, emerging evidence suggests that the buildup of nuclear DNA damage, especially DNA double-strand breaks (DDSBs), plays a key role in contributing neurodegeneration, promoting senescence and neuroinflammation. Despite the pathogenic role for DDSB in neurodegenerative disease, targeting DNA repair mechanisms in PD is largely unexplored as a therapeutic approach. Ataxia telangiectasia mutated (ATM), a key kinase in the DNA damage response (DDR), plays a crucial role in neurodegeneration. In this study, we evaluated the therapeutic potential of AZD1390, a highly selective and brain-penetrant ATM inhibitor, in reducing neuroinflammation and improving behavioral outcomes in a mouse model of α-synucleinopathy. Four-month-old C57BL/6J mice were unilaterally injected with either an empty AAV1/2 vector (control) or AAV1/2 expressing human A53T α-synuclein to the substantia nigra, followed by daily AZD1390 treatment for six weeks. In AZD1390-treated α-synuclein mice, we observed a significant reduction in the protein level of γ-H2AX, a DDSB marker, along with downregulation of senescence-associated markers, such as p53, Cdkn1a, and NF-κB, suggesting improved genomic integrity and attenuation of cellular senescence, indicating enhanced genomic stability and reduced cellular aging. AZD1390 also significantly dampened neuroinflammatory responses, evidenced by decreased expression of key pro-inflammatory cytokines and chemokines. Interestingly, mice treated with AZD1390 showed significant improvements in behavioral asymmetry and motor deficits, indicating functional recovery. Overall, these results suggest that targeting the DDR via ATM inhibition reduces genotoxic stress, suppresses neuroinflammation, and improves behavioral outcomes in a mouse model of α-synucleinopathy. These findings underscore the therapeutic potential of DDR modulation in PD and related synucleinopathy.